2012
DOI: 10.1002/cbdv.201100359
|View full text |Cite
|
Sign up to set email alerts
|

A New Era of the Vaginal Microbiome: Advances Using Next‐Generation Sequencing

Abstract: Until recently, bacterial species that inhabit the human vagina have been primarily studied using organism-centric approaches. Understanding how these bacterial species interact with each other and the host vaginal epithelium is essential for a more complete understanding of vaginal health. Molecular approaches have already led to the identification of uncultivated bacterial taxa associated with bacterial vaginosis. Here, we review recent studies of the vaginal microbiome and discuss how culture-independent ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
61
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 105 publications
2
61
0
3
Order By: Relevance
“…High-throughput sequencing methods have facilitated new lines of investigation into the microbial etiology of PTB (9,10). Amplification and high-throughput sequencing of the 16S rRNA gene (metabarcoding) simultaneously measures the presence and relative abundance of thousands of bacterial taxa (composition), and resolves differences to the level of genus and sometimes species or subspecies.…”
mentioning
confidence: 99%
“…High-throughput sequencing methods have facilitated new lines of investigation into the microbial etiology of PTB (9,10). Amplification and high-throughput sequencing of the 16S rRNA gene (metabarcoding) simultaneously measures the presence and relative abundance of thousands of bacterial taxa (composition), and resolves differences to the level of genus and sometimes species or subspecies.…”
mentioning
confidence: 99%
“…Since the first microbiological study of the human vagina, lactobacilli have been considered the dominant members of the microbiota of this organ (Doderlein, 1982), a finding that has been further confirmed by several recent metagenomic studies (Biagi et al, 2009;Fettweis et al, 2012;Martín et al, 2014;Pavlova et al, 2002;Song et al, 1999;Verhelst et al, 2004;Vitali et al, 2007;Wilks et al, 2004;Zhou et al, 2004). In total, around 20 different species of lactobacilli have been consistently isolated from the vagina, although only one or two species predominate at a time in a given individual.…”
Section: Introductionmentioning
confidence: 92%
“…Although several recent studies have described the vaginal microbiome [18], only a recent study, sampling DNA isolated from exfoliated cervical cells, has shown the existence of six cervical microbiome community types, characterized by a predominance of either Gardnerella vaginalis or Lactobacillus spp. [29].…”
Section: Cervical and Vaginal Microbiome Characterizationmentioning
confidence: 99%
“…This mixed community of microbial cells and the genes they contain, is collectively known as the microbiome. The total number of microbial cells found in the human body is ten times more than those of human cells [18,19,20], and the total number of genes associated with the human microbiome is considered more than 100 times the number of human genes [20]. The NIH launched the Human Microbiome Project in 2007 in order to understand human microbial communities [20,21].…”
Section: Next-generation Sequencing In the Study Of The Human Microbiomementioning
confidence: 99%